Existential of Freedom in Artistic and Journalist Practice of Volodymyr Vynnychenko (by the Example of Publication «V.Vynnychenko about Himself and about the Ukrainian «Odnobichnyky») - Vitaliy Matsko (Pedagogical Discourse, 2013)
The article deals with the world outlook position of V.Vynnychenko that is characterized by the synthesis of contradictory approaches to interpreting common to mankind values, to abtaining liberty. Through the rational explanation of man’s nature, vision of the writer social processes and phenomena, we find ourselves in the space of existentional philosophy: inner disappointment, despair, estrangement, which breaks through in the form of contemplations about the sense of living. The article reveals the inner world in V.Vynnychenko dialogical discourse, conversation with the correspondent of the newspaper «Ukrainian news». In the interview the writer calls the reasons of the fall UPR, which are focused in the light of Vynnychenko’s concordism and discordism (coordination and disorder) among the Ukrainian public figures and decision-makers.